Faktor-Faktor Yang Mempengaruhi Minat Siswa Kelas XII Mengikuti Ekstrakurikuler Ekonomi Akuntansi di SMAN1 Kuta Utara - Suparini, Komang; Indrayani, Luh (Jurnal Pendidikan Ekonomi Undiksha, 2023)
This study aims to find out the factors that affect the interest of students of class XII IPS following extracurricular accounting economics. This research is a type of quantitative research. The population and sample used are 144 students of class XII IPS SMAN 1 North Kuta. The data collection method used is a questionnaire. The data that has been collected is then analyzed using factor analysis techniques. The results showed that the factors that affect students following the extracurricular accounting economics consist of two factors, namely physical internal factors, intelligence, talent, maturity, and motivation, and external factors consisting of attention, family environment, and school environment. The most dominant factor influencing students' interests is motivation.